FACTORS RELATED TO THE PRACTICE OF SELLING LIMITEDRESTRICTED OTC DRUGS IN SMALL SHOPS IN NORTH OBA DISTRICTIN 2025 - Sitti Hartinah; mardia habel; Sulviati Fidia Ningsih (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Based on data obtained from the Tidore Islands City Health Office, an inspection was conducted on kiosks/small stalls/stalls in several areas of North Oba District in 2023. The inspection results showed that of the 96 kiosks/small stalls in North Oba District, 74 (77%) were found to be selling restricted over-the-counter drugs despite not having a permit as a legal drug kiosk. The purpose of this study was to determine the factors related to the practice of selling restricted over-the-counter drugs in small stalls. This type of research used quantitative research with a descriptive design.cross sectional.There are four variables that have a relationship with the practice of selling restricted over-the-counter drugs: knowledge (p = 0.001), social environment (p = 0.003), economy (p = 0.000), supervision (p = 0.000). The knowledge of business actors and residents in the social environment greatly influences the practice of selling restricted over-the-counter drugs by business actors in small shops. Poor knowledge of both sellers and buyers about the dangers of restricted over-the-counter drugs sold without a doctor's prescription is still very high. In addition, low economic conditions and government supervision of the distribution of restricted over-the-counter drugs in small shops without official permits are among the factors that continue to be widespread in the practice of selling restricted over-the-counter drugs.